Influenсe of different factors on sorption of ⁹⁰Sr by natural and synthetic zeolites - Lonin, A.Yu.; Krasnopyorova, A.P. (Вопросы атомной науки и техники, 2005)
The paper researches into factors influencing sorption and selective properties of natural zeolite clinoptilolite
from the Sokirnitsky deposit of Ukraine and synthetic zeolites in relation to radionuclide ⁹⁰Sr. It also studies the
effect of competing ions on the sorption of ⁹⁰Sr by zeolites. Досліджено фактори, що впливають на сорбційно-селективні властивості природного цеоліту
клиноптилолита Сокирницького родовища України і синтетичних цеолітів щодо радіонукліда
⁹⁰Sr. Показано,
що наявність конкуруючих іонів суттєво знижує сорбцію
⁹⁰Sr цеолітами. Исследованы факторы, влияющие на сорбционно-селективные свойства природного цеолита
клиноптилолита Сокирницкого месторождения Украины и синтетических цеолитов относительно
радионуклида
⁹⁰Sr. Показано, что при наличии конкурирующих ионов существенно снижается сорбция ⁹⁰Sr
цеолитами